1996
DOI: 10.1021/cm960373s
|View full text |Cite
|
Sign up to set email alerts
|

Ionochromic and Thermochromic Phenomena in a Regioregular Polythiophene Derivative Bearing Oligo(oxyethylene) Side Chains

Abstract: Structural, thermal, and optical studies on regioregular poly[3-oligo(oxyethylene)-4-methylthiophene] have revealed interesting thermochromic and ionochromic effects related to a planar/nonplanar transition of the conjugated backbone. This first-order-like conformational transition (formation of twistons) seems driven by side-chain disordering induced by an increase of temperature or through noncovalent interactions with specific cations. The twisting of one repeat unit of this regioregular polythiophene deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 32 publications
6
78
0
1
Order By: Relevance
“…If PMThO derivatives were a regiorandom structure in the polymer backbone, 16 sets of 13 C resonances are detected. 9,12,18,19 The 13 C NMR spectrum of PMThO derivatives supports the interpretation of the 1 H NMR data. 1 H NMR and 13 C NMR data of PMThO derivatives demonstrate that PMThO derivatives with regioregular structure in the polymer backbone can be easily obtained by the conventional oxidative polymerization using iron trichloride as a catalyst.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…If PMThO derivatives were a regiorandom structure in the polymer backbone, 16 sets of 13 C resonances are detected. 9,12,18,19 The 13 C NMR spectrum of PMThO derivatives supports the interpretation of the 1 H NMR data. 1 H NMR and 13 C NMR data of PMThO derivatives demonstrate that PMThO derivatives with regioregular structure in the polymer backbone can be easily obtained by the conventional oxidative polymerization using iron trichloride as a catalyst.…”
Section: Resultssupporting
confidence: 64%
“…Leclerc et al reported that regioregular 3,4-disubstituted PTh derivatives were obtained by chemical oxidation of the relative monomers by iron trichloride. [14][15][16][17][18][19] This method is very easy way to obtain regioregular PTh derivatives compared to the synthetic methods using Rieke zinc y To whom correspondence should be addressed (Tel: +81-3-5228-8248, Fax: +81-3-3235-2214, E-mail: nkoide@ch.kagu.sut.ac.jp). or nickel catalyzed cross-coupling.…”
mentioning
confidence: 99%
“…[167] This type of discovery is yet another indication that regioregularity is an important factor in the development of ionoselective sensors.…”
Section: Chemically Prepared Alkoxy Pts As Conducting Polymer Sensorsmentioning
confidence: 96%
“…Upon heating, an absorption band at 560 nm related to a planar (or nearly planar) conjugated backbone showed a decrease, meanwhile a new absorption band located at 446 nm appeared and gradually increased with increasing the heating temperature. The latter is characteristic of a delocalized twisted (less conjugated) form of the polythiophene backbone [14]. This absorbance change is fully reversible, and, upon cooling, the COP64 film recovers its initial absorption spectrum.…”
Section: Resultsmentioning
confidence: 96%